Whole genome sequencing identifies a homozygous nonsense mutation in the JPH2 gene in Shih Tzu dogs with progressive retinal atrophy. (6th July 2021) - Urkasemsin, G.; Pongpanich, M.; Sariya, L.; Kongcharoen, A.; Buddhirongawatr, R.; Rungarunlert, S.; Ferreira, J. N.; Chetruengchai, W.; Phokaew, C.; Srichomthong, C.; Shotelersuk, V.
Summary: Progressive retinal atrophy (PRA), common autosomal recessive disorder affecting several dog breeds including Shih Tzu, is characterized by degeneration of photoreceptors leading to blindness. To identify PRA genetic variants, three affected and 15 unaffected Shih Tzu and 20 non‐Shih Tzu were recruited. Dogs underwent ophthalmologic examination and electroretinography, revealing hallmark retina pathological changes and an abnormal electroretinography in all affected dogs but not in unaffected dogs. WGS was performed. Non‐synonymous homozygous variants were searched in coding regions of genes involved in retinal diseases/development; the criterion was that variants should only be present in affected dogs and should be absent in both unaffected and 46 genomes of dogs (from an available evolutionary database). Only one out of the 109 identified variants is predicted to harbor a high‐impact consequence, a nonsense c.452A>C (p.L151X) in the JPH2 gene. The genotype of JPH2 variant in all 38 dogs was determined with Sanger sequencing. All three affected dogs, but none of the 35 unaffected, were homozygous for the nonsense variant. JPH2 has been previously found to be expressed in several excitable cells/tissues including retina photoreceptors. Hence, JPH2 is a candidate gene for PRA in Shih Tzu.